Polymyxin-B hemoperfusion for acute exacerbation of idiopathic pulmonary fibrosis: serum IL-7 as a prognostic marker - Tachibana, K.; Inoue, Y.; Nishiyama, et al., A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: Acute exacerbation (AE) of idiopathic pulmonary fibrosis (IPF) has an extremely poor prognosis. Direct hemoperfusion with a polymyxin B-immobilized fiber column (PMX-DHP) has been used to improve oxygenation for acute respiratory distress syndrome.The study aim was to retrospectively determine the predictive factors affecting the prognosis of AE of IPF treated with PMX-DHP. Methods:We studied patients suffering from AE of IPF, treated with PMX-DHP combined with high-dose corticosteroid therapy. Stored serum taken before and after PMX-DHP therapy was analyzed for 27 cytokines and chemokines. Results: Nineteen patients with AE of IPF were studied. The median survival time after diagnosis of AE was 22 days. Survival rates after diagnosis of AE were 47.4% at 30 days, 31.6% at 60 days, and 26.3% at 90 days. Serum levels of Interleukin (IL)-7, an anti-fibrotic cytokine, in survivors at day 30 following PMX-DHP therapy (‘Survivors’) significantly increased after the treatment, compared to serum levels of non-survivors at day 30 after the therapy (‘Nonsurvivors’), which did not demonstrate a significant change. Serum levels of IL-1β, interferon-γ and chemokine ligand (CCL) 2 levels were not significantly altered in ‘Survivors,’ but were significantly changed in ‘Nonsurvivors.’ Multivariate Cox proportional-hazards analysis showed that an increase in IL-7 levels after PMX-DHP therapy and treatment without intubation (other than invasive positive-pressure ventilation) were significantly better prognostic factors. Conclusion: The results suggest that serum IL-7 may be a useful prognostic factor for patients with AE of IPF treated with PMX-DHP, possibly reflecting underlying anti-fibrotic mechanisms.